2019
DOI: 10.1111/1460-6984.12512
|View full text |Cite
|
Sign up to set email alerts
|

Semantic fluency difficulties in developmental dyslexia and developmental language disorder (DLD): poor semantic structure of the lexicon or slower retrieval processes?

Abstract: Background Children with dyslexia and/or developmental language disorder (hereafter children with DDLD) have been reported to retrieve fewer words than their typically developing (TD) peers in semantic fluency tasks. It is not known whether this retrieval difficulty can be attributed to the semantic structure of their lexicon being poor or, alternatively, to words being retrieved more slowly despite semantic structure being intact. Aims To test two theoretical models that could potentially account for retrieva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 56 publications
(125 reference statements)
1
5
0
1
Order By: Relevance
“…Moreover, findings remain limited to languages other than English, although language characteristics can affect performance in tasks tapping on lexical access and vocabulary development [ 63 ]. In line with our results on semantic fluency (yet, contrast to findings in studies with English-speaking children [ 100 , 101 ]), a recently published study [ 102 ] found poorer semantic fluency in Greek-speaking school-age children with DLD relative to TD peers. However, researchers did not additionally obtain a phonological fluency measure.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, findings remain limited to languages other than English, although language characteristics can affect performance in tasks tapping on lexical access and vocabulary development [ 63 ]. In line with our results on semantic fluency (yet, contrast to findings in studies with English-speaking children [ 100 , 101 ]), a recently published study [ 102 ] found poorer semantic fluency in Greek-speaking school-age children with DLD relative to TD peers. However, researchers did not additionally obtain a phonological fluency measure.…”
Section: Discussionsupporting
confidence: 91%
“…Besides, controversial findings remain limited in languages other than English. A recently published study in the language of the present sample (one of the very few in Greek; see Mengisidou et al [ 102 ]) found poorer semantic fluency performance in school-age children with DLD relative to TD peers; yet, researchers have not also used a phonological fluency measure.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…According to researchers, children with DLD do not present a consistent language profile since their language characteristics show great heterogeneity ( Pijnacker et al, 2017 ). Previous studies have documented difficulties on the part of the DLD population in non-word repetition ( Bishop et al, 1996 ; Baddeley et al, 1998 ; Larkin et al, 2013 ; Lalioti et al, 2016 ; Mengisidou et al, 2020 ), in verbal short-term memory ( Hill, 2001 ; Girbau and Schwartz, 2007 ) as well as impairments in terms of working memory and processing speed ( Archibald and Gathercole, 2006 ; Leonard, 2014 ). In addition, they face problems in phonological awareness and in oral language production, including many grammatical errors.…”
Section: Introductionmentioning
confidence: 99%
“…The difficulties individuals with DLD face concern nonword repetition (Baddeley, Gathercole, & Papagno, 1998;Bishop, North, & Donlan, 1996;Lalioti, Stavrakaki, Manouilidou, & Talli, 2016;Mengisidou, Marshall, & Stavrakaki, 2020), phonological awareness, oral speech production (Catts & Kahmi, 1986), reading and verbal short-term memory (Girbau & Schwartz, 2007;Hill, 2001). Deficits are also observed in morphology (Abel, Rice, & Bontempo, 2015;Rice, Wexler, & Cleave, 1995;van der Lely & Ullman, 2001), and especially in the use of passive voice (van der Lely, 1996) and in question clauses (Stavrakaki, 2019;van der Lely & Battell 2003).…”
Section: 2 Developmental Language Disordermentioning
confidence: 99%